Evaluation of the DAVIH-RAPID-BRU Immunochromatographic Test for Diagnosing Brucellosis in Swine Herds - Santana, Yanelis Cruz; Herrera, Dervel Felipe Diaz; Alfonso, Dayamí Martín; Sui , Otto Cruz; Quintero , Anitza Fragas; Tamayo, Lucy Montano (Journal of Applied Veterinary Science And Technology, 2025)
Background: The diagnosis of Brucella spp. traditionally requires complex serological tests that demand a well-equipped laboratory and trained personnel. To overcome these limitations, the Veterinary Diagnostic and Research Laboratories (DAVIH) developed a lateral flow immunochromatographic system capable of detecting antibodies in serum or whole blood, facilitating its use under field conditions without the need for sophisticated infrastructure. Purpose:  Evaluate the performance of the rapid immunochromatographic test in swine herds. Method: A total of 348 blood samples were collected from the marginal ear vein of swine (323 females and 25 males) from farms with a high prevalence of brucellosis. The results of the rapid test using whole blood (field) and serum (laboratory) were compared against the reference standard. Diagnostic validity indicators, predictive values, and the Kappa index were calculated to assess agreement between tests. Results: The test demonstrated high sensitivity (95.26% in blood; 98.95% in serum) but moderate specificity (81.65% in blood; 84.81% in serum). The agreement between blood and serum results was good (Kappa = 0.78), although 7.5% of the samples showed discordant results, possibly due to interference from blood components. Negative predictive values were excellent (93.48% in blood; 98.53% in serum), indicating high reliability for ruling out infections. The test also showed robustness under variable environmental conditions. Conclusion: The DAVIH-RAPID-BRU system is a rapid, sensitive, and practical tool for the initial screening of swine brucellosis in the field, particularly useful for epidemiological surveillance programs. However, due to its moderate specificity, positive cases should be confirmed with more specific tests (such as 2-ME or RFC) to avoid misdiagnosis. Its implementation could significantly enhance early detection efforts in endemic areas.